COMMISSIVE SPEECH ACT IN DONALD TRUMP’S SPEECH CAMPAIGN - Desriani Gea (Universitas Hasanuddin, 2020)
Commissive speech acts focus to carry out the speaker toward particular action in the future. The speech of Donald Trump in campaign rally at Nevada has function to convey his vision and mission as candidate president in second time. This research purposes to find the types of commissive speech act and understand the functions of commissive speech act in Donald Trump’s speech campaign in Henderson, Nevada on 13 September 2020. The orientation in this research refer to utterance of Donald trump, The data source of this research take from video’s Fox Business in YouTube. This research used descriptive qualitative, with technique of collecting data are observation, watching and take note. The result of this research, there are 28 commissive speech acts in different functions. The result indicates 8 types commisive speech act by utterance of Donald Trump, there are promise, threaten, swear, guarantee, warrant, refuse, assure and vow.